Impact of Psychological Factors on Academic Attainment: A Study of Anxiety and Emotional Intelligence Among B.Ed. Trainees - Kanchan Pandey; Dr. Alok kumar Mishra (Innovative Research Thoughts, 2025)
Within the scope of this study, the influence of psychological elements, more specifically anxiety and emotional intelligence, on the academic accomplishments of B.Ed. trainees is specifically investigated. Understanding the ways in which emotional intelligence and anxiety influence academic performance can assist educators, institutions, and politicians in developing effective support programs. This is especially important in this day and age, when mental well-being is being increasingly acknowledged as an essential component of how well students do in school. Standardized instruments, such as the Emotional Intelligence Scale (EIS) and the State-Trait Anxiety Inventory (STAI), were utilized in order to conduct a survey conducted on a sample of two hundred B.Ed. trainees from a variety of universities. The results of university examinations were used to evaluate the students' academic performance. A strong negative link was found between anxiety and academic accomplishment, while a positive correlation was found between emotional intelligence and academic success. The findings suggested that both of these correlations were significant. In order to improve students' academic performance, the findings highlight the importance of including emotional and psychological support systems into programs that are designed to educate teachers.